Risco e pânico moral: uma análise sociológica do "medo do crime" na revista Superinteressante (2008-2012). - Bitencourt, Antonio Belamar Oliveira de (2013)
This study, a sociological perspective, has aimed to investigate the possible existence of a relation between the social phenomena fear of crime and moral panic. The study was realized through a research in Superinteressante magazine. Its purpose is to understand how this magazine emphasizes in its reports/articles the issues/themes which contain the concepts of fear of crime , risk and moral panic as central issues. The first concept, fear of crime , is based in Borges (2011) and Glassner ([1999] 2003), being portrayed as a social construction. The second concept, risk, is based in Giddens ([1990] 1991), where it is conceived as more individual, and in Beck ([1986] 2010) where it is global. The third and last concept, moral panic , is guided by the ideal classification of Goode & Ben-Yehuda ([1994b] 2009). The research has the hypothesis that the fear of crime here treated as a social phenomenon and derived from a social construction influences negatively in the conception of risk of potential criminal victimization. Therefore, there is a direct relationship between fear of crime and moral panic, with risk being present in this discussion, either directly or indirectly.